Exploratory factor analysis of two most widely used materialism measurements - Saffana, Kuni; Puri, Valendra Granitha Shandika; Hidayat, Rahmat (Institute of Advanced Engineering and Science, 2024)
The material value scale (MVS) and the aspiration index (AI) are among the most prominent measurements of materialism in research. As the names indicate, the MVS measures materialism in terms of materialistic values, whereas AI measures it in the matter of aspirations. Although both instruments have been widely used in research, the question of whether materialistic values and aspirations are independent of each other remains open for examination. The answer to this question is important, considering the inconsistencies in the results of past research. Therefore, this study aims to assess the construct's similarity and dissimilarity between both self-report materialism measurements resulting from exploratory factor analysis (EFA). The study was conducted online in Indonesia in 2019, with 610 participants, Indonesian version of MVS and AI, the software of Jamovi and R Studio. The analysis consisted of the Bartlett test, Kaiser-Meyer-Olkin test, parallel analysis, minimum rank factor analysis, EFA, and reliability (Cronbach’s α). The result showed there was an intersection, but each measurement had a portion of each independence higher, hence was no sufficient evidence of similarity between both materialism constructs. The construct of materialism as value and materialism as aspiration is proposed as different. Limitations of the study and implications for research were discussed.